Developing Young Children’s Multingualism and Pluriculturalism - TITONE, Renzo (Wydawcnictwo Naukowe UAM, 1994)
Multilingual and pluricultural education are strictly tied together. A definition of the basic ideas concerning both processes implies the clarification of several issues: 1. The study of foreign culture within language; 2. The understanding of divergent cultural patterns; 3. Cultural differences in nonverbal communication; 4. Understanding art of a different culture; 5. The training of teachers for intercultural and interlinguistic education. The final word of success rests in well-planned experimental projects, i.e. long range research on an international basis.